2003
DOI: 10.12968/ijpn.2003.9.6.11511
|View full text |Cite
|
Sign up to set email alerts
|

Professionals’ views and experiences of using outcome measures in palliative care

Abstract: In palliative care, outcome measures are increasingly used to aid clinical practice, conduct audit and research. The objective of this study was to elicit professionals' views and experiences of using outcome measures, paying special attention to the Palliative care Outcome Scale (POS). This article presents the results of a qualitative study of 26 professionals, experienced in using the POS, who were invited to participate in semi-structured telephone interviews. Of those invited, 22 people took part. Partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
49
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 6 publications
2
49
0
Order By: Relevance
“…Some participants noted that the POS was difficult to use when patients were too ill and that 'some patients feel that it is very intrusive' or found it 'confusing and upsetting'. 344 Some professionals also reported that they found some of the questions 'difficult to ask' or found the responses 'difficult to deal with'. 344 In response to this, the authors described how some professionals had altered the questions, ranging from 'vocabulary changes, to making more substantial revisions such as reworking questions or, in some cases, omitting certain questions and including new ones'.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some participants noted that the POS was difficult to use when patients were too ill and that 'some patients feel that it is very intrusive' or found it 'confusing and upsetting'. 344 Some professionals also reported that they found some of the questions 'difficult to ask' or found the responses 'difficult to deal with'. 344 In response to this, the authors described how some professionals had altered the questions, ranging from 'vocabulary changes, to making more substantial revisions such as reworking questions or, in some cases, omitting certain questions and including new ones'.…”
mentioning
confidence: 99%
“…344 In response to this, the authors described how some professionals had altered the questions, ranging from 'vocabulary changes, to making more substantial revisions such as reworking questions or, in some cases, omitting certain questions and including new ones'. 344 For example, one participant explained how they had omitted one of the questions to improve its usability in their local setting:…”
mentioning
confidence: 99%
“…The specialist nurses were concerned about the timing of use of the SCC and had concerns about some of the items on the SCC and wished to avoid causing additional distress to patients (Hopkinson et al, 2006;Hughes et al, 2003). Patients may feel violated if they have shared sensitive information prematurely or against their wishes (Widang and Fridlund, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The barriers to using such tools in terms of specialist nurse attitudes need to be considered. Evidence of the effectiveness of the tools such as the SCC in terms of patient outcomes are needed as well as a consideration of training needs when incorporating these tools into practice (Hughes et al, 2003;Slater and Freeman, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation